PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN PADA TOKO GALERI BATIK ANJANI-KOTA BATU - Faras Ridhwan; Theobaldus Boro Tura (Journal of Research and Publication Innovation, 2025)
The purpose of this research is to determine the influence of workload and compensation on employee performance at Toko Galeri Batik Anjani-Kota Batu, both partially and simultaneously. This study uses a quantitative descriptive research method, objectively examining a situation using numerical data, with data collection techniques through questionnaires. The sample used is non-probability sampling with a saturated sampling technique from 62 employees. The data analysis method used is hypothesis testing research, utilizing SPSS version 27. The results of the research show that the variables of workload and compensation have a significant influence on employee performance at Toko Galeri Batik Anjani-Kota Batu, both partially and simultaneously. Based on the partial statistical test or t-test, the calculated t-value is 3.912 > 1.6706. This means that Ha1 is accepted, and Ho1 is rejected, indicating that workload significantly affects employee performance. As for compensation, the partial t-test obtained a calculated t-value of 4.931 > 1.6706. This means that Ha2 is accepted, and Ho2 is rejected, indicating that compensation affects employee performance. Simultaneously, the calculated F-value is 147.091 > F-table 2.761 with a significance level of 0.000 < α 0.05, indicating that Ho3 is rejected, and Ha3 is accepted. This means that workload and compensation simultaneously have a positive and significant influence on employee performance. This shows that the percentage of the influence of workload and compensation on employee performance is 83.3%, with the remaining 16.7% influenced or explained by other variables outside of those studied.